(untitled) (Research, Society and Development, 2022)
Approximately 30% of females have suffered violence, whether sexual, physical, or psychological by their partners, framing themselves as victims of domestic violence. The objective of this work carried out in the form of a narrative review of the literature is to discuss women in the history of Brazil, conceptualize domestic violence, explain the Maria da Penha Law and its applicability, epidemiology of injuries to the face, profile of the victim and the aggressor, the most prevalent types of injuries in the face of these victims, and diagnosis of injuries. The research showed that the pattern of these women is between 20 and 30 years old, black, financially dependent. When dealing with aggressors, it is common for it to be the husband/partner. In order to minimize these numbers, in 2006 Law 11,340 was enacted, which aims to protect this citizen, therefore, after the increment of this legislation, individuals who commit the crime of domestic violence against this gender are punished as described in the Law. The facial injuries characteristic of this type of violence are soft tissue trauma such as lacerations, abrasion, contusion and hematoma; dento-alveolar traumas such as extrusive dislocation, subluxation, concussion, coronary fracture, avulsion, and alveolar fracture. In more severe cases involving bone fractures, the nasal bone, mandible and zygomatic complex. It is common for the first contact of these victims to be with a health professional, so the dental surgeon must be attentive and able to identify and notify the competent bodies.